2019
DOI: 10.2147/opth.s189260
|View full text |Cite
|
Sign up to set email alerts
|

360° ab-interno trabeculotomy in refractory primary open-angle glaucoma

Abstract: PurposeThe purpose of this study was to evaluate the safety and efficacy of microinvasive glaucoma surgery (MIGS) with 360° ab-interno trabeculotomy using the TRAB360 device as a stand-alone procedure in patients with refractory primary open-angle glaucoma (POAG) and preoperative IOP ≥18 mmHg.SettingThis study evaluated patients treated in a tertiary-referral clinical practice setting.DesignThis study is a retrospective analysis of 81 eyes.MethodsPatients with refractory open-angle glaucoma underwent stand-alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Secondary outcome measures included the proportion of eyes achieving target IOPs of ≤18 mmHg and ≤15 mmHg, mean IOP and medication reduction, and any complications or additional IOP-lowering procedures needed. For this analysis, an IOP spike was defined as IOP >30 mmHg at any time point, and a steroid response was defined as IOP ≥28 mmHg and >25% increased from baseline while on topical prednisolone with subsequent IOP reduction >25% upon discontinuation of prednisolone 19. Early postoperative reflux microhyphema is common to all angle surgeries and was noted but was not considered an adverse event within the first 2 postoperative weeks, unless it required treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary outcome measures included the proportion of eyes achieving target IOPs of ≤18 mmHg and ≤15 mmHg, mean IOP and medication reduction, and any complications or additional IOP-lowering procedures needed. For this analysis, an IOP spike was defined as IOP >30 mmHg at any time point, and a steroid response was defined as IOP ≥28 mmHg and >25% increased from baseline while on topical prednisolone with subsequent IOP reduction >25% upon discontinuation of prednisolone 19. Early postoperative reflux microhyphema is common to all angle surgeries and was noted but was not considered an adverse event within the first 2 postoperative weeks, unless it required treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It is reasonable to hypothesize that IOP reduction would be proportional to the extent of diseased TM bypassed to allow aqueous to flow into the distal outflow system. Under such a hypothesis, a 360° trabeculotomy—as can be accomplished by Trab360 (Sight Sciences, Inc., Menlo Park, CA)9 or gonioscopy-assisted transluminal trabeculotomy (GATT)10—should produce greater IOP reductions than the ~120° excisional goniotomy accomplished using the KDB. To address this issue, we report a 6-month retrospective comparison of KDB excisional goniotomy versus 360° trabeculotomy (either Trab360 or GATT) in combination with cataract performed at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to evaluation of MIGS procedures in PG, prior work has been published evaluating ab interno trabeculotomy procedures with a trabectome in this population including a study by Akil et al that demonstrated comparable efficacy of the trabectome device comparing eyes with PG and POAG, highlighting the potential value of angle‐based MIGS procedures in PG. In addition, studies evaluating other forms of ab interno trabeculotomy have included eyes with PG . Given the paucity of peer‐reviewed data focused on the use of the trabecular micro‐bypass stent in PG, we hope this study conveys valuable information regarding the trabecular micro‐bypass stent with cataract surgery in patients with PG.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve (12) female Dutch Belted rabbits, aged 4 to 5 months, were purchased from Covance (Denver, CO). MINIject was implanted in the right eye (Test group) of each animal, while the left eye had no implant nor other operation (Control group).…”
Section: Time-course Biointegration Studymentioning
confidence: 99%
“…Such devices are intended to promote the drainage of aqueous humor from the anterior chamber towards the physiological conventional (e.g. iStent and iStent inject from Glaukos, Hydrus from Ivantis, Trabectome or Goniotome from MicroSurgical Technology, Kahook Dual Blade from New World Medical, OMNI or VISCO360 or TRAB360 from Sight Sciences, ABiC from Ellex) [4,[7][8][9][10][11][12][13] or uveoscleral (e.g. CyPass from Alcon, iStent Supra from Glaukos, MINIject from iSTAR Medical) [7,14,15] pathways, or to the non-physiological subconjunctival location (XEN from Allergan, PRESERFLO Micro-Shunt from Santen) [4,16,17].…”
Section: Introductionmentioning
confidence: 99%